2021
DOI: 10.3390/toxics9020023
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment Induced by Lead Exposure during Lifespan: Mechanisms of Lead Neurotoxicity

Abstract: Lead (Pb) is considered a strong environmental toxin with human health repercussions. Due to its widespread use and the number of people potentially exposed to different sources of this heavy metal, Pb intoxication is recognized as a public health problem in many countries. Exposure to Pb can occur through ingestion, inhalation, dermal, and transplacental routes. The magnitude of its effects depends on several toxicity conditions: lead speciation, doses, time, and age of exposure, among others. It has been dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(49 citation statements)
references
References 190 publications
3
46
0
Order By: Relevance
“…Through this and the previous work Lucchini et al 2019, we were able to observe an association of Pb on both behavior and cognition. These adverse effects of Pb were also showed by other studies 34 , 35 and were associated to alterations in DNA and chromosomal integrity, interaction with proteins 36 and alteration to cellular redox status 37 .…”
Section: Discussionsupporting
confidence: 70%
“…Through this and the previous work Lucchini et al 2019, we were able to observe an association of Pb on both behavior and cognition. These adverse effects of Pb were also showed by other studies 34 , 35 and were associated to alterations in DNA and chromosomal integrity, interaction with proteins 36 and alteration to cellular redox status 37 .…”
Section: Discussionsupporting
confidence: 70%
“…Epidemiological studies have reported that chronic exposure to As through drinking water results in impaired development of intellectual function in children, as well as reduced sensory and motor function [ 7 , 8 ]. Likewise, Pb exposure is known to be related to cognitive impairment, executive function alterations, and fine motor control perturbations [ 9 ]. In addition, increased blood Cd is reported to be associated with worsened cognitive function and motor skills [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lead is a toxic heavy metal in different sources such as contaminated drinking water, battery manufacture, cosmetics, leaded gasoline, lead-based paint, cans, glazed ceramics, traditional herbal medicine products, water pipes, jewelry, tobacco smoke, and electronic cigarettes, and toys. Lead exposure can be considered a public health concern, especially in early childhood, because children have increased hand-to-mouth activity, so they are more at risk [13,14]. While the half-life of Pb in the bloodstream is about 35 days, it is stored in bones for approximately 30 years [15,16].…”
Section: Leadmentioning
confidence: 99%